DAMPAK PANDEMI COVID-19 TERHADAP PENGHAYATAN IMAN ORANG MUDA KATOLIK - Juniati, Antonia Juniati; Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2022)
Catholic youth are a generation that is highly relied on by the Church, in this case the Church places great hopes on the Catholic youth to become a pillar of church life, both in the present and in the future. One of them is the phenomenon of the Covid-2019 (Covid-19) pandemic which has an impact on so many aspects of life. The massive impact due to the adjustment and handling of the Covid-19 pandemic touched on the activities of efforts to live up to the faith of the Catholic Youth. The vulnerability situation that occurred during the Covid-19 pandemic in addition to having an impact on the physical and mental, the Covid-19 pandemic also damaged the concept of community. Keywords: The Impact Of Covid-19, The Appreciation Of Faith, Catholic Youth.